Arizona Water Resource Vol. 17 No. 1 (September-October 2008) - University of Arizona. Water Resources Research Center. (Water Resources Research Center, College of Agriculture, University of Arizona (Tucson, AZ), 2008)
Includes supplement: Arizona NEMO: Watershed Projects and Programs === With desalination looming big on the water resource horizon, many water officials are looking at their options. One option Arizona officials are considering is building a desalination plant in Puerto Penasco that would be a joint Mexican-Arizona project, with both the resort community and the state benefiting from the desalinated water supplies.